Chemostratigraphy and U-Pb age constraints of Mesoproterozoic carbonate successions of the Río de la Plata Craton, Uruguay - Gaucher, Claudio; Sial, Alcides; Frei, Roberto; Frei, Dirk; Poire, Daniel Gustavo; Bossi, Jorge
A belt consisting of volcanosedimentary successions exhibiting greenschist-facies metamorphism is exposed in the Nico Pérez Terrane, eastern Río de la Plata Craton (RPC) in Uruguay. The Parque UTE Group (PUG) con- sists of basic volcanics and gabbros at the base (1492+4 Ma, U-Pb on zircon), carbonates in its middle part, and interbedded carbonates, shales and acid volcanics (1429+21 Ma, U-Pb on zircon) at the top. The overlying Mina Verdún Group (MVG) is made up of rhyolites and acid pyroclastics at its base and top, and Conophyton-bearing limestones and massive dolostones in the middle (Poiré and Gaucher, 2009). Fil: Gaucher, Claudio. Universidad de la República; Uruguay Fil: Sial, Alcides. Universidad de Pernambuco; Brasil Fil: Frei, Roberto. Universidad de Copenhagen; Dinamarca Fil: Frei, Dirk. Geological Survey of Denmark and Greenland; Dinamarca Fil: Poire, Daniel Gustavo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Investigaciones Geológicas. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Investigaciones Geológicas; Argentina Fil: Bossi, Jorge. Facultad de Agronomía; Uruguay 18th International Sedimentological Congress Mendoza Argentina International Association of Sedimentologists